Rationally Designed Energy Transfer in Upconverting Nanoparticles. (24th March 2015) - Chan, Emory M.; Levy, Elizabeth S.; Cohen, Bruce E.
<x xml:space="preserve">Abstract</x> Significant advances in the analysis and theoretical modeling of upconverting nanoparticles (UCNPs) are beginning to reveal the complex details of their energy transfer (ET) pathways. UCNPs combine multiple NIR photons to emit at higher energies in the NIR or visible, and are an ideal system for the rational design and precise engineering of optical processes. The ET pathways that drive photon upconversion can be tuned by varying the combination of lanthanide co‐dopants, their concentrations, and their spatial distribution within the nanocrystal. Here, recent work is reviewed on the development of complex UCNP architectures that segregate lanthanides across multiple domains in a heterostructure or within the unit cell of the host lattice. These designs direct ET in UCNPs to enhance their brightness, to maximize desired emission wavelengths, to suppress undesirable electronic transitions, and to sensitize absorption of light at different wavelengths. The development of holistic computational models for ET in UCNPs is yielding novel nanocrystal designs with unexpected properties, such as UCNPs with exceptional brightness at single molecule imaging powers. These rational approaches for engineering ET will accelerate the development of UCNPs tailored to specific nanophotonic applications that require the efficient and directed flow of energy.